Knowledge and beliefs about nutrition and physical activity during pregnancy in women from South Auckland region, New Zealand. (14th March 2016) - Okesene‐Gafa, Karaponi; Chelimo, Carol; Chua, Shireen; Henning, Marcus; McCowan, Lesley
Abstract : Background: Approximately 60% of women in South Auckland, a culturally diverse region in New Zealand, become pregnant with a high body mass index. However, little is known about these women's knowledge of nutrition and physical activity during pregnancy. Aims: To assess knowledge of nutrition and physical activity during pregnancy, factors influencing eating habits and the willingness to participate in a nutritional intervention. Materials and Methods: A total of 422 women completed the survey in late pregnancy between September and December 2013. Multivariable logistic regression investigated factors associated with infrequent healthy eating, adjusting for ethnicity and gestation at questionnaire completion. Results: Ethnicity of participants was Māori (24.2%), Pacific (40.5%), Asian (12.8%) and European/Others (21.8%). Most (95.0%) reported receiving information about healthy eating while pregnant and 61% reported eating healthy frequently or very frequently. Forty‐four point three per cent reported eating more in pregnancy; the commonest reasons were cravings and 'eating for two'. The adjusted odd ratios (aORs) indicated that the self‐reported factors associated with infrequent healthy eating in this sample were Māori (aOR 17.66; 95% CI 8.49–36.77) and Pacific ethnicity (aOR 14.54; 95% CI 7.32–28.88); parity ≥3 (aOR 2.09; 95%CI 1.26–3.48); obesity (aOR 2.84; 95% CI 1.35–5.97); unplanned pregnancy (aOR 1.95; 95%CI 1.18–3.22); and eating takeaways ≥3 times/week (aOR 4.46; 95%CI 1.88–10.56). Of women sampled, 83.4% would likely/very likely participate in a nutritional intervention. Conclusion: Self‐reported factors associated with infrequent healthy eating in pregnancy were identified in this sample. Our findings will assist development of a nutritional intervention for pregnant women in South Auckland.